1988
DOI: 10.1177/000992288802700301
|View full text |Cite
|
Sign up to set email alerts
|

Seizures in the Neonatal Intensive Care Unit of the 1980s

Abstract: A retrospective review was taken of 150 newborns with seizures evaluated at the same medical center and by the same investigator(s) from 1982 to 1987. The aims of the study were to determine in this current population the distribution of clinical seizure types, the distribution of causative etiologies, and the relation of etiology to the timing of onset of the seizures. Seizures were classified as subtle, multifocal clonic, generalized tonic, focal clonic, and myoclonic. Subtle (65% of total) and multifocal cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 4 publications
4
22
2
Order By: Relevance
“…8 Calciolari et al reported 8 cases of neonatal seizures with primary metabolic abnormalities, out of which 38 % had hypoglycemia, 50 % had hypocalcemia and 12.5 % had hyponatremia. 9 In this study, 29 (55.76%) of 52 babies presenting with seizures having electrolyte abnormalities were associated with HIE, IVH and meningitis/sepsis. Hyponatremia 18 (62.06%) is the most common electrolyte disturbance found in these cases of secondary biochemical abnormalities.…”
Section: Discussionmentioning
confidence: 57%
“…8 Calciolari et al reported 8 cases of neonatal seizures with primary metabolic abnormalities, out of which 38 % had hypoglycemia, 50 % had hypocalcemia and 12.5 % had hyponatremia. 9 In this study, 29 (55.76%) of 52 babies presenting with seizures having electrolyte abnormalities were associated with HIE, IVH and meningitis/sepsis. Hyponatremia 18 (62.06%) is the most common electrolyte disturbance found in these cases of secondary biochemical abnormalities.…”
Section: Discussionmentioning
confidence: 57%
“…Seizure type Calcialari Et Al [12] In the present study, out of 59 neonates 69.49% cases had single seizure type, Subtle seizure were most common in 27.11 % of cases, focal clonic in 13.55 %, multifocal 11.86%, Generalized tonic 3.39% and myoclonic in 8.47% of the cases. Combined type of seizure activity was observed in 30.51 % of cases, of these subtle and mutlifocal variety was observed in 13.55% of cases, subtle and generalized tonic 5.08%, Subtle and focal clonic in 6.77% of cases.…”
Section: Clinical Profilesupporting
confidence: 43%
“…Combined type of seizure activity was observed in 30.51 % of cases, of these subtle and mutlifocal variety was observed in 13.55% of cases, subtle and generalized tonic 5.08%, Subtle and focal clonic in 6.77% of cases. Calciolari et al in 1987 [12] from, Washington, reported single seizure type in 50% of cases and combined type in 50%.. Of single seizure type, subtle seizure were more common in 21%…”
Section: Clinical Profilementioning
confidence: 97%
“…The severity of neurological symptoms is directly correlated with the duration of metabolic disturbances (42). Hypocalcemia nowadays account for about 3% of all cases of neonatal seizures, mostly are focal and occurs in the first 72 hours of life (29,43). Most common causes are low birth weight especially those associated with intrauterine growth retardation, infants of diabetic mothers, and hypoxic ischemic encephalopathy.…”
Section: Causesmentioning
confidence: 99%